Association of the Membrane-Penetrating Polypeptide Segment of the Human Erythrocyte MN-Glycoprotein with Phospholipid Bilayers. I. Formation of Freeze-Etch Intramembranous Particles - Segrest, Jere P. (1974)
The membrane-penetrating segment of the surface MN-glycoprotein of the human erythrocyte is contained intact within the tryptic peptide T(is). We report here on the association of this peptide with hydrated phospholipid vesicles. Under these conditions 80 Å intramembranous particles, as seen by freeze-etch electron microscopy, are produced that are similar in size to those seen in the native erythrocyte membrane. These particles increase in number as a linear function of T(is) concentration and a plot of particle number versus concentration is compatible with a micelle-like phenomenon; from this curve the critical concentration for the formation of particles is estimated to be approximately one mole of T(is) to 120 moles of lecithin. These data suggest that the membrane-penetrating peptide T(is) is being incorporated, monomerically and multimerically, within the hydrocarbon phase of lecithin bilayers. From these data it can be calculated that each intramembranous particle contains between 10 and 20 T(is) monomers. The peptide portion of each particle, therefore, has a molecular weight of 45,000-85,000. An exact analogy cannot be drawn at this time between the in vivo structure of erythrocyte intramembranous particles and the reconstituted particles described here, although an argument has been constructed to support this possibility. What is clear is that the reconstituted system promises to be useful for further examination of protein-lipid interactions in membranes.